Restricting Arranged Marriage Opportunities for Danish Minority Youth: Implications for Criminal Convictions - Andersen, Lars Højsgaard (Journal of quantitative criminology, 2022)
Objectives To measure the effect of arranged marriages on criminal convictions among male ethnic minority youth in Denmark. Methods To identify the effect, we rely on administrative data from before and after a national policy reform in 2002 that restricted ethnic minority youths’ access to their most prevalent type of marriage until both spouses were at least 24 years of age. We use difference-in-differences estimation and meticulously analyze potential time trends in the data. Results Although the reform substantially decreased marriage rates in both the short (24 percent decrease at age 24) and longer (10 percent at age 30) run, this reform effect produced no response in criminal conviction risks in neither short nor long run. Conclusion Criminologists discuss whether social institutions, such as marriage, influence desistance from crime or whether the association is driven by unobserved heterogeneity. Several empirical strategies have been proposed to settle the discussion. Our contribution to this line of research is an alternative empirical strategy that relies on a natural experiment. Our study focuses only on one specific type of marriage in one context and focuses on criminal convictions rather than behavior per se—which are important limitations. Still, results uniformly reject the hypothesis that the marriages in our study influenced criminal convictions.